Age-related deficits in efficiency of low-level lateral inhibition - Schlaghecken, Friederike; Birak, Kulbir S.; Maylor, Elizabeth A. (Frontiers in Human Neuroscience, 2012)
Background: In a masked prime task using a 0 ms prime-target inter-stimulus-interval, responses on trials where prime and target match (compatible trials) are usually faster and more accurate than responses where prime and target mismatch (incompatible trials). This positive compatibility effect (PCE) comprises both behavioral benefits on compatible relative to neutral trials, and behavioral costs on incompatible relative to neutral trials. Comparing performance in 2- vs. 4-alternative-response versions of the task indicates that benefits are due to direct priming (i.e., pre-activation) of a motor response, whereas costs reflect an inhibition of the alternative response tendency. The present study employs this paradigm to test the hypothesis that normal aging is associated with a selective deficit in inhibitory function, affecting both low-level motor and higher-level executive control. Experiment and Results: Testing 20 young and 20 older healthy adults, we found that (1) overall, prime-induced benefits were of similar magnitude across age groups, but inhibition-based costs were smaller in older compared to young adults; (2) increasing the number of response alternatives caused the same pattern of unaltered benefits and reduced costs in both age groups; and (3) costs, but not benefits, in the 2-alternative condition were significantly predicted by scores on the digit symbol substitution task (DSST), independently of age and other background variables. Interpretation: Results demonstrate the possibility of isolating an inhibitory component in low-level perceptuo-motor control. Importantly, this component shows an age-related decline in the absence of a corresponding decline of visuo-motor excitability, and appears to be linked to performance on a higher-level processing speed task. We hypothesize that aging might affect the brain's ability to establish precise short-term lateral inhibitory links, and that even in young adults, the efficiency of such links is a significant contributing factor in higher-level cognitive performance.